2014
DOI: 10.1002/jmri.24578
|View full text |Cite
|
Sign up to set email alerts
|

Inlet and outlet valve flow and regurgitant volume may be directly and reliably quantified with accelerated, volumetric phase‐contrast MRI

Abstract: Purpose To determine whether it is feasible to use solely an accelerated 4D-PC MRI acquisition to quantify net and regurgitant flow volume through each of the cardiac valves. Materials and Methods Accelerated, 4D-PC MRI examinations performed between March 2010 through June 2011 as part of routine MRI examinations for congenital, structural heart disease were retrospectively reviewed and analyzed using valve-tracking visualization and quantification algorithms developed in Java and OpenGL. Excluding patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 33 publications
1
64
1
2
Order By: Relevance
“…25 Westenberg et al 93 demonstrated that the assessment of tricuspid flow and regurgitation volumes from 4D PC data with retrospective manual alignment of multiplanar reconstructed tricuspid valvular imaging planes enables more accurate quantification of tricuspid flow volume, regurgitation volume and regurgitation fraction than does the use of 2D PC imaging. Roess et al 94 and Hsiao et al 95 analyzed flow and regurgitation volumes through all cardiac valves in healthy controls and patients with diverse valvular and shunt pathologies and found highly consistent results.…”
Section: Phase-contrast Indices Of Ventricular Functionmentioning
confidence: 91%
“…25 Westenberg et al 93 demonstrated that the assessment of tricuspid flow and regurgitation volumes from 4D PC data with retrospective manual alignment of multiplanar reconstructed tricuspid valvular imaging planes enables more accurate quantification of tricuspid flow volume, regurgitation volume and regurgitation fraction than does the use of 2D PC imaging. Roess et al 94 and Hsiao et al 95 analyzed flow and regurgitation volumes through all cardiac valves in healthy controls and patients with diverse valvular and shunt pathologies and found highly consistent results.…”
Section: Phase-contrast Indices Of Ventricular Functionmentioning
confidence: 91%
“…Due to the medical development and increasing life expectancy, the number of surgeries and interventions is expected to rise [1, 2]. Currently, surgical aortic valve replacement with biological or mechanical prostheses is the standard of care in most cases of aortic stenosis [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the application of kt-GRAPPA with R=5 allowed acquiring the 4D flow protocol in less than 11 minutes, other approaches may need to be explored (and potentially combined) to further accelerate data acquisition for clinical application. Such approaches could include increasing the number of coil elements to achieve higher acceleration factors (15,45), applying radial acquisitions with high undersampling factors as in PC-VIPR (16), or using compressed sensing methods (2022). Besides the acquisition time for the 4D flow protocol also the total session time is a limiting factor: in this work a period of 2.5–3 hours was required, including the setup, tuning/matching the RF coil elements, B1+ mapping, performing calibration routines, calculating B1+ shim solutions, and acquiring the 4D flow data.…”
Section: Discussionmentioning
confidence: 99%
“…Also, non-Cartesian acquisition techniques such as PC-VIPR have been successfully applied resulting in scan times below 10 minutes (16). Further shortening of the acquisition time can be achieved by accelerating along the spatial and temporal dimension using kt-BLAST, kt-SENSE and kt-GRAPPA (1719), or by applying compressed sensing techniques (2022). Applying both temporal and spatial acceleration is a promising route to achieve short total acquisition time while pushing towards higher resolution.…”
Section: Introductionmentioning
confidence: 99%